La significación de la discriminación por los homosexuales a partir de estereotipos de género en la familia (2019)
The aim of the present investigation was to analyze the significance of homosexual persons opposite to the discrimination based on the stereotypes of kind on the part of the family, this one itself was registered inside the qualitative descriptive method of investigation. The investigation had support from theoretical investigations, semi-structured interviews, utilization of images and others, which favored the boarding of the individuality of every participant before the discrimination towards the homosexual in his life, different tools were in use in order to have records that benefited the major profit of the information. Finally a categorization of the information was realized then to give him an analysis objective detailed and later the conclusion of the investigation. One thought that the stereotypes of kind fulfill a very important paper in the discrimination on the part of the family towards homosexual persons and that this population decides to isolate, to hide his sexual preference or to ignore this type of discrimination for which they it turns out slightly very negative that brings repercussions psicoemocionales, and it puts them in conflict with it same.